Immune response dynamics of SARS-CoV-2 vaccination in chronic lymphocytic leukemia individuals: a descriptive analysis - Sánchez-Menéndez, Clara; Zurdo, Alejandro; Corona, Magdalena; Mateos de la Morenas, Elena; Rodríguez-Mora, Sara; Casado, Guiomar; García-Pérez, Javier; Pérez-Olmeda, Mayte; Domínguez, Susana; Murciano-Antón, María Aránzazu; López-Jiménez, Javier; García-Gutiérrez, Valentín; et al. (Frontiers in Immunology, 2025)
Chronic lymphocytic leukaemia (CLL) is a lymphoproliferative disorder of abnormal B-lymphocytes. Due to immune deregulation and therapy-related factors, CLL individuals face increased infection risks, making vaccination a priority. Although COVID-19 is no longer a global emergency, understanding vaccine responses in this vulnerable population, especially those undergoing active cancer treatments, remains critical for broader infectious disease prevention strategies. We have characterized the humoral and cellular immune response of SARS-CoV-2 vaccination elicited by CLL individuals under standard-of-care treatment and watch and wait (W&W) strategy compared with healthy subjects who received a three-dose regimen six months ago. Seroconversion rates varied between 81.8% and 71.4% in individuals under W&W and dropped to 28.6%-22.2% in those under treatment, with antibody titres and neutralizing activity following the same pattern, highlighting the impact of active therapies on vaccine immunogenicity. Analysis of B-cell dynamics revealed that individuals under W&W maintained the highest levels of total B cells (CD19+) throughout the study (up to 3.5-fold higher than healthy donors, p<0.0001). Basal naïve B cells were markedly reduced across CLL groups (up to 4.3-fold lower in treated vs. W&W, p<0.0001), while memory subsets expanded over time, particularly in the W&W cohort after booster vaccination. Additionally, we found that the actively treated CLL group exhibited higher levels of cytotoxic cells (including CD8+ T cells and NK cells) when compared to the W&W or the healthy population groups. However, none of these cell populations demonstrated an increased activation capacity. Moreover, the direct cytotoxic capacity of peripheral blood mononuclear cells (PBMCs) from CLL persons was also more efficient in the W&W group. Through our comprehensive characterization of both humoral and cellular immune responses in CLL individuals, this study provides insight into the complex immunological landscape following SARS-CoV-2 vaccination. Our detailed analysis supports the current vaccination strategy against SARS-CoV-2 for CLL patients, confirming its effectiveness and underscoring the importance of close monitoring and representing a significant advancement in our understanding of immune responses in hematological malignancies.